Micro/Nano-Chip Electrokinetics, Volume III - Xuan, Xiangchun; Qian, Shizhi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Micro/nanofluidics-based lab-on-a-chip devices have found extensive applications in the analysis of chemical and biological samples over the past two decades. Electrokinetics is the method of choice in these micro/nano-chips for transporting, manipulating, and sensing various analyte species (e.g., ions, molecules, fluids, and particles). This book aims to highlight the recent developments in the field of micro/nano-chip electrokinetics, ranging from the fundamentals of electrokinetics to the applications of electrokinetics to both chemo- and bio-sample handling.